Depression Level Of Adolescent In Banyuwangi Based On Gender Using Beck Depression Inventory-II - Purwoningrum, Ary's Kusumaayu (Tadulako University, 2020)
Depression can interfere with the mood that affects a person's feelings, thinking ability, and completing daily activities. Symptoms of depression include prolonged sadness and loss of interest in doing activities that are usually done, followed by a decrease in the ability to carry out activities. Based on data from WHO in 2015, the proportion of the global population experiencing depression is estimated at 4.4%. Meanwhile, based on a survey from Riskesdas in 2018 showed that depression began to occur in the 15-24 year age group with a prevalence of 6.2%. Adolescents are an age group that is vulnerable to depression. This study aims to determine the level of depression in students of OSIS management of vocational high schools (SMK) in Banyuwangi based on gender using BDI-II (Beck Depression Inventory-II). This research is a descriptive type of research with a quantitative approach using a total population of 51 people of the student organization management of vocational high schools (SMK) in Banyuwangi. The questionnaire used is BDI-II (Beck Depression Inventory-II) which consists of 21 statements. The respondents' answers were categorized into 4 levels of depression categories, namely no depression, mild depression, moderate depression and major depression. Male students who did not depression were 41.7%, mild depression were 16.6%, moderate depression were 41.7%, and major depression were 0%. The female students who did not depression were 56.4%, mild depression were 35.9%, moderate depression were 7.7%, and major depression were 0%. Depression is more common in women than men